Asymmetric cell division of stem cells in the lung and other systems - Berika, Mohamed; Elgayyar, Marwa E.; El-Hashash, Ahmed H. K. (Frontiers in Cell and Developmental Biology, 2014)
New insights have been added to identification, behavior and cellular properties of embryonic and tissue-specific stem cells over the last few years. The modes of stem cell division, asymmetric versus symmetric, are tightly regulated during development and regeneration. The proper choice of a stem cell to divide asymmetrically or symmetrically has great consequences for development and disease because inappropriate asymmetric division disrupts organ morphogenesis, whereas uncontrolled symmetric division induces tumorigenesis. Therefore, understanding the behavior of lung stem cells could identify innovative solutions for restoring normal morphogenesis and/or regeneration of different organs. In this concise review, we describe recent studies in our laboratory about the mode of division of lung epithelial stem cells. We also compare asymmetric cell division in the lung stem cells with other tissues in different organisms.